2002
DOI: 10.1021/bi016029c
|View full text |Cite
|
Sign up to set email alerts
|

Use of an in Situ Disulfide Cross-Linking Strategy To Map Proximities between Amino Acid Residues in Transmembrane Domains I and VII of the M3 Muscarinic Acetylcholine Receptor

Abstract: In this study, we employed an in situ disulfide cross-linking strategy to gain insight into the structure of the inactive and active state of the M(3) muscarinic acetylcholine receptor. Specifically, this study was designed to identify residues in TM I that are located in close to Cys532 (position 7.42), an endogenous cysteine residue present in the central portion of TM VII. Cysteine residues were substituted, one at a time, into 10 consecutive positions of TM I (Ala71-Val80) of a modified version of the M(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 52 publications
3
60
0
2
Order By: Relevance
“…1). In agreement with a recently developed three-dimensional model of the M 3 muscarinic receptor (27), we demonstrated previously that Cys-532 is located adjacent to the ligand-binding pocket projecting into the center of the TM receptor core (29). Specifically, we examined whether Cys-532 is able to form activity-dependent crosslinks with Cys residues introduced into the exofacial segment of TM III (Leu-142 3.27 -Asn-152 3.37 ) (see Fig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…1). In agreement with a recently developed three-dimensional model of the M 3 muscarinic receptor (27), we demonstrated previously that Cys-532 is located adjacent to the ligand-binding pocket projecting into the center of the TM receptor core (29). Specifically, we examined whether Cys-532 is able to form activity-dependent crosslinks with Cys residues introduced into the exofacial segment of TM III (Leu-142 3.27 -Asn-152 3.37 ) (see Fig.…”
supporting
confidence: 90%
“…Transfected cells were incubated with atropine (1 M) for the last 24 h of culture. Previous studies have shown that this atropine incubation step significantly increases the expression levels of Cys-substituted mutant M 3 muscarinic receptors (26,27,29).…”
Section: Characterization Of Mutant M 3 Muscarinic Receptors In Radiomentioning
confidence: 93%
See 1 more Smart Citation
“…Disulfide trapping has been used to demonstrate the spatial arrangement of dimers of the E. coli aspartate receptor (26), bacterial Trg chemoreceptor (27), and the above-mentioned dopamine D2 receptor (18); this technique has also been applied to the analysis of intramolecular contacts between transmembrane domains of GPCRs, such as the M 3 muscarinic receptor (28). In this study, we demonstrate that the oxidation of endogenous C5aR molecules in human neutrophils results in disulfide-linked dimers.…”
mentioning
confidence: 75%
“…Ala 291(7.42) and Phe 301(7.52) lie parallel to each other on the same helix face mostly facing the same area of the binding pocket. Ala 291(7.42) is predicted to face the protein interior, a feature that seems to be highly conserved among GPCRs, because this position also points inside the binding pocket of the D2 dopamine receptor, M3 muscarinic receptor, A2 adenosine receptor, and rhodopsin (21)(22)(23)(24). Phe 301(7.52) is part of a classical ␣-helical segment underlying the conserved NPXXY motif following the helical deviation.…”
Section: Discussionmentioning
confidence: 99%